+0  
 
0
34
2
avatar+24 

Find the value of (1+i)^16

grif389  Oct 7, 2018
 #1
avatar
0

Simplify the following:
(i + 1)^16

Compute (1 + i)^16 by repeated squaring. For example a^7 = a a^6 = a (a^3)^2 = a (a a^2)^2.
(1 + i)^16 = ((i + 1)^8)^2 = (((i + 1)^4)^2)^2 = ((((i + 1)^2)^2)^2)^2:
((((i + 1)^2)^2)^2)^2

Expand (i + 1)^2.
(i + 1)^2 = 1 + i + i - 1 = 2 i:
(((2 i)^2)^2)^2

Evaluate (2 i)^2.
(2 i)^2 = -4:
((-4)^2)^2

Evaluate (-4)^2.
(-4)^2 = 16:
16^2

Evaluate 16^2.
=256

Guest Oct 7, 2018
 #2
avatar+28 
+1

To write what he just said in a way that is easier to see,

 

\((1+i)^{16} = ((i+1)^{8})^{2} = (((i+1)^{4})^{2})^{2} = ((((i+1)^{2})^{2})^{2})^{2}\)

 

Now if we expand and solve for \((i+1)^{2}\), we get:

 

\(i^2+2i+1 = -1+2i+1 = 2i\)

 

Therefore, \(((((i+1)^{2})^{2})^{2})^{2} = (((2i)^2)^2)^2\)

 

Since \(i = -\sqrt1\)  ,   \((2i)^2 = -4\)

 

Therefore, \((((2i)^2)^2)^2 = ((-4)^2)^2\)

 

Evaluating \(((-4)^2)^2\), we get \((16)^2\)

 

\(16^2=256\), so \(\boxed{256}\) is our answer

 

smiley

KnockOut  Oct 7, 2018

28 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.